Proposition of a transdiagnostic processual approach of emotion dysregulation based on core triggers and interpersonal styles - Blay, Martin; Duarte, Miguel; Dessouli, Marie-Alix; Durpoix, Amaury; Rüfenacht, Eva; Weibel, Sébastien; Speranza, Mario; Perroud, Nader (Frontiers in Psychiatry, 2024)
Emotion dysregulation (ED) has primarily been described in patients suffering from borderline personality disorder (BPD) and is an integral part of this diagnosis, but it is also a transdiagnostic construct that can be found in several other psychiatric disorders. The strong relationships between ED and BPD may lead clinicians to underestimate ED associated to other clinical contexts. This can lead to difficulties in diagnostic and treatment orientation, especially in the context of comorbidities. In this article, after reviewing the literature on the development and functioning of emotion dysregulation, and on the evidence for emotion dysregulation in eight disorders (borderline personality disorder, pathological narcissism with/without narcissistic personality disorder, obsessive-compulsive personality disorder, antisocial personality disorder, bipolar disorder, autism spectrum disorder, complex post-traumatic stress disorder, and adult attention deficit hyperactivity disorder), we present a transdiagnostic processual model of emotion dysregulation based on core triggers and interpersonal styles to try to address this issue and to provide a simple but technical tool to help clinicians in their diagnostic assessment and treatment orientation. By focusing more on typical patterns and interpersonal dynamics than only on categories, we believe that this model may contribute to the actual need for improvement of our current psychiatric classifications, alongside other well-studied and under-used dimensional models of psychopathology (e.g., HiTOP, AMPD), and may be useful to build more specific treatment frameworks for patients suffering from ED.